Pengaruh struktur kepemilikan terhadap volume perdagangan saham pada laporan keuangan tahunan Perusahaan LQ-45 - Hajrah Hamzah; Nur Afiah (Seminar Nasional LP2M UNM, 2019)
This study aims to determine (1) the influence of institutional ownership, foreign ownership partially on the volume of stock trading in the LQ-45 company's annual financial statements, (2) the effect of institutional ownership, simultaneous foreign ownership of stock trading volume on LQ company's annual financial statements -45. The method of data collection uses purposive sampling in LQ-45 companies listed on the Indonesia Stock Exchange (IDX) for 2016. Until 2017. The research data was obtained from www.idx.co.id. From 51 companies obtained a sample of 27 companies or 54 years of company data This study uses multiple linear regression. The results of the study show that institutional ownership influences the volume of trading in the company's shares. Institutional ownership in general can act as a party that monitors the company. A high level of institutional ownership will lead to greater oversight efforts by institutional investors so that it can hinder manager's opportunistic behavior. Foreign ownership affects the volume of trading in company shares. The percentage of shares owned by high international investors has an impact on effective monitoring efforts. This will increase the value and performance of the company because it can control the opportunistic behavior of managers that make managers reduce debt levels optimally.